Cross-sectional survey of the undergraduate rheumatology curriculum in European medical schools: a EULAR School of Rheumatology initiative. Issue 2 (21st September 2018) - Abhishek, Abhishek; Iagnocco, Annamaria; Bijlsma, J W J; Doherty, Michael; Lioté, Frédéric
Abstract : Objectives: To survey the undergraduate rheumatic and musculoskeletal diseases (RMDs) curriculum content in a sample of medical schools across Europe. Methods: The undergraduate musculoskeletal diseases and disability curriculum of University of Nottingham, UK, was used as a template to develop a questionnaire on curriculum content. The questionnaire elicited binary (yes/no) responses and included the option to provide additional information as free text. The survey was mailed to members of the European League Against Rheumatism (EULAR) School of Rheumatology (Undergraduate Classroom) and to EULAR Standing Committee on Education and Training members in January 2017, with a reminder in February 2017. Results: Responses were received from 21 schools belonging to 11 countries. Assessment of gait, hyperalgesic tender site response and hypermobility were not included in many curricula. Similarly, interpretation of investigations undertaken on synovial fluid was taught in only 16 schools. While disease-modifying anti-rheumatic drugs and biological agents, and urate-lowering treatment were included in the curricula of 20 and 21 institutions, respectively, only curricula from 18 schools included core non-pharmacological interventions. Osteoarthritis, gout, rheumatoid arthritis, spondyloarthropathy, polymyalgia rheumatica and lupus were included in the curriculum of all institutions. However, common RMDs such as calcium pyrophosphate deposition, fibromyalgia, giant cell arteritis and bone and joint infection were included in 19 curricula. Conclusion: This survey highlights areas of similarities and differences in undergraduate curricula across Europe. It is hoped that the results of this survey will catalyse the development and agreement of a minimum core European Curriculum for undergraduate education in RMDs.